Redesign of workstations guitar product to minimize musculoskeletal disorders for workers - Pratiwi, Indah; Jannah, Isnainiyah Wardatul (Operations Excellence: Journal of Applied Industrial Engineering, 2024)
The production process of acoustic guitars in Indonesia involves 4 workstations and 17 distinct activities. Due to the nature of the work—8-hour shifts in seated positions with frequent bending, squatting, and repetitive movements—workers are at risk of musculoskeletal disorders (MSDs), particularly in the neck, shoulders, back, arms, and wrists. This study aimed to identify and analyze body posture conditions using the Nordic Body Map (NBM) and Muscle Fatigue Analysis (MFA) methods. The NBM method was used to record pain complaints across various body parts, while the MFA assessed muscle fatigue by considering the level of effort, work duration, and movement frequency. Results from the NBM showed that among the workers, 2 were at high risk, 3 at medium risk, and 7 at low risk for MSDs. The MFA further identified 3 workers with very high to high-priority fatigue concerns, specifically affecting the neck, back, shoulders, right arm, wrist, and legs. To address these issues, the study recommended redesigning work facilities and layouts using the SolidWorks application, along with implementing regular muscle stretching and exercise routines to minimize the risk of MSDs and improve worker well-being.